Practicing the Extension in Software Engineering Education: an Experience Report - Colanzi, Thelma; Silva, Leandro; Medeiros, Andressa; Gonçalves, Paulo; Souza, Eniuce; Farias, Douglas; Amaral, Greicy (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
University Extension is an educational, cultural, and scientific process that establishes the exchange between academic and popular knowledge. Project-Based Learning (PjBL) consists of allowing students to confront the issues and problems of the world through a real project. PjBL has been adopted in Software Engineering (SE) teaching to motivate and engage students in studying and applying processes and methods. In this work, the university extension was integrated with the PjBL in teaching SE in a postgraduate course to bring students closer to real practices of software development, meeting a demand from the State of notorious value for society. Interviews were conducted with stakeholders, artifacts were delivered, and students received feedback from the professor and the stakeholders. Through a questionnaire, the students provided feedback about the practical activity, the learning method, and their perceptions regarding their evolution and dedication to group work. We can highlight the following findings: (i) the use of PjBL together with extension and the development of a real project was promising for the evolution of learning; (ii) greater motivation of the students, who evaluated: (iii) the learning method as satisfactory, and (iv) the practical activity and their evolution of learning as good and excellent. Our main contribution is the lessons learned that might guide future experiences that adopt PjBL in SE teaching and extension.